2022
DOI: 10.1007/s00134-022-06677-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of dexamethasone 12 mg versus 6 mg in patients with COVID-19 and severe hypoxaemia

Abstract: Purpose:We assessed long-term outcomes of dexamethasone 12 mg versus 6 mg given daily for up to 10 days in patients with coronavirus disease 2019 (COVID-19) and severe hypoxaemia. Methods:We assessed 180-day mortality and health-related quality of life (HRQoL) using EuroQoL (EQ)-5D-5L index values and EQ visual analogue scale (VAS) in the international, stratified, blinded COVID STEROID 2 trial, which randomised 1000 adults with confirmed COVID-19 receiving at least 10 L/min of oxygen or mechanical ventilation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…The COVID STEROID 2 trial was an investigator-initiated, international, parallel-group, blinded randomised clinical trial). (3-5) Detailed descriptions of the trial methods, interventions, outcomes, statistical analyses, and the results for the COVID STEROID 2 trial have been published elsewhere. (3-5) In brief, 1000 adult patients hospitalised with COVID-19 and severe hypoxaemia (requiring ≥10 L oxygen/minute or mechanical ventilation) were enrolled from 31 sites in 26 hospitals in Denmark, India, Sweden and Switzerland between 27 August 2020 and 20 May 2021.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID STEROID 2 trial was an investigator-initiated, international, parallel-group, blinded randomised clinical trial). (3-5) Detailed descriptions of the trial methods, interventions, outcomes, statistical analyses, and the results for the COVID STEROID 2 trial have been published elsewhere. (3-5) In brief, 1000 adult patients hospitalised with COVID-19 and severe hypoxaemia (requiring ≥10 L oxygen/minute or mechanical ventilation) were enrolled from 31 sites in 26 hospitals in Denmark, India, Sweden and Switzerland between 27 August 2020 and 20 May 2021.…”
Section: Methodsmentioning
confidence: 99%
“…(3-5) Detailed descriptions of the trial methods, interventions, outcomes, statistical analyses, and the results for the COVID STEROID 2 trial have been published elsewhere. (3-5) In brief, 1000 adult patients hospitalised with COVID-19 and severe hypoxaemia (requiring ≥10 L oxygen/minute or mechanical ventilation) were enrolled from 31 sites in 26 hospitals in Denmark, India, Sweden and Switzerland between 27 August 2020 and 20 May 2021. Patients were randomised 1:1 to dexamethasone 12 mg or 6 mg intravenously (IV) once daily for up to 10 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent multinational randomised controlled trial found that 12 mg dexamethasone may be more beneficial than the typically employed 6 mg dose. 10 …”
Section: The Changes In the Characteristics Of The Pandemic And In Ou...mentioning
confidence: 99%
“…The impact of adopting beneficial treatments identified by clinical trials needs to be examined in more detail, to determine, for example, the appropriate use of prone ventilation or the optimal steroid dose. A recent multinational randomised controlled trial found that 12 mg dexamethasone may be more beneficial than the typically employed 6 mg dose 10 …”
mentioning
confidence: 99%